CURAHAN TENAGA KERJA KELUARGA PETANI PADI SAWAH LAHAN PASANG SURUT DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Linda Harahap; Zulkifli Alamsyah; Rozaina Ningsih (Agros Journal of Agriculture Science, 2024)
This study aims to analyze 1) the distribution of family labor, 2) family income based on the allocation of distribution of labor, non-tidal rice farming and non-agricultural businesses, 3) factors that influence the labor of tidal rice farmers low tide in Kumpeh District, Muaro Jambi Regency. Pematang Raman Village and Tanjung Village were determined as samples purposively. The total sample was 86 farmers, data processing was carried out quantitatively. The research results showed that the total outflow of farmer labor was 187 HOK/year, which was distributed by 12.1 percent to rice farming, 18.9 percent to non-rice farming and 64.0 percent to non-agricultural businesses. The average farming family income is IDR. 8,532,658/year, rice farming in tidal fields amounting to Rp. 11,255,814/year, non-rice farming of Rp. 13,874,535/year, non-agricultural businesses with the highest contribution of 41.2 percent in non-agricultural businesses. Land area, number of family dependents, level of education and rice farming income have a positive and real influence on the amount of labor, while the farmer's age factor has a negative influence on the amount of farmer's working hours.